A preliminary assessment of geological CO2 storage in the Khorat Plateau, Thailand - Chenrai, Piyaphong; Jitmahantakul, Sukonmeth; Bissen, Raphael; Assawincharoenkij, Thitiphan (Frontiers in Energy Research, 2022)
The main carbon dioxide (CO2) emissions in Thailand come from the energy sector. Gas-based power plants, including natural gas and biogas, are CO2 point sources, and are mostly located in the Khorat Plateau. Geological CO2 storage is an important element in the effort to reduce CO2 emissions from CO2 point sources. This study is a preliminary assessment of the geological CO2 storage potential of the onshore Khorat Plateau. A potential geological formation is screened and ranked in terms of its suitability as a CO2 storage site (storage optimization, risk minimization and feasibility). The results of this screening and ranking indicate that, among the tested sites in this study, the Khorat Permian carbonate is the most suitable for geological CO2 storage, followed by the Khorat Group sandstone, and Khorat evaporite. However, the Khorat Cenozoic basalts are not suitable for geological CO2 storage in the Khorat Plateau. The results from this study should advance the understanding of petroleum exploration and carbon capture and storage technology in Thailand, especially in the Khorat area. However, it should be noted that more subsurface studies are needed, and more criteria should be included in the future to improve the reliability of the assessment of geological CO2 storage potential in the Khorat Plateau.